A Phase II Study to Assess the Safety and Efficacy of the Dual mTORC1/2 and PI3K Inhibitor Bimiralisib (PQR309) in Relapsed, Refractory Lymphoma. Issue 11 (27th November 2021) - Collins, Graham P.; Eyre, Toby A.; Schmitz-Rohmer, Debora; Townsend, William; Popat, Rakesh; Giulino-Roth, Lisa; Fields, Paul A.; Krasniqi, Fatime; Soussain, Carole; Stathis, Anastasios; Andjelkovic, Nebojsa; Cunningham, David; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Bimiralisib is an orally bioavailable pan-phosphatidylinositol 3-kinase and mammalian target of rapamycin inhibitor which has shown activity against lymphoma in preclinical models. This phase I/II study evaluated the response rate to bimiralisib at 2 continuous dose levels (60 mg and 80 mg) in patients with relapsed/refractory lymphoma. Fifty patients were enrolled and started treatment. The most common histologies were diffuse large B-cell lymphoma (n = 17), follicular lymphoma (n = 9), T-cell lymphoma (n = 8), and others (mostly indolent). Patients had been treated with a median of 5 prior lines of treatment and 44% were considered refractory to their last treatment. Mean duration of treatment (and standard deviations) with 60 mg once daily (o.d.) was 1.3 ± 1.2 months, and with 80 mg o.d. 3.7 ± 3.9 months. On an intention to treat analysis, the overall response rate was 14% with 10% achieving a partial response and 4% a complete response. Thirty-six percent of patients were reported as having stable disease. No dose-limiting toxicities were observed during the phase I portion of the study. Overall, 70% of patients had a grade 3 treatment emergent adverse events (TEAE) and 34% had a grade 4 TEAE; 28% of patients discontinued treatment due to toxicity. The most frequent TEAEs grade ≥3 was hyperglycemia (24%), neutropenia (20%), thrombocytopenia (22%), and diarrhea (12%). Per protocol, hyperglycemia required treatment with oral antihyperglycemic agents in 28% and with insulin in 14%. At 60 mg or 80 mg continuous dosing, bimiralisib showed modest efficacy with significant toxicity in heavily pretreated patients with various histological subtypes of lymphoma.